Comparative Pharmacological and Phytochemical Evaluation of Raw and Herb-Processed Salt Formulations - Rakulini, S. (Postgraduate Institute of Indigenous Medicine, University of Colombo, 2026)
Salt obtained from terrestrial, marine, or botanical sources possesses distinct antiperiodic, emetic, laxative, stomachic, and vermifuge properties supporting its widespread application in traditional therapies. In Siddha medicine dietary regulation (Pathiyam) is divided into Itchapathiyam and Kadumpathiyam is fundamental to therapeutic success, requiring strict salt restriction during and after treatment. In post- treatment protocols typically involve external applications of omum-cow's milk paste alongside dietary inclusion of roasted salt combined with cow's ghee and tamarind. Furthermore, traditional practitioners process salt by frying it with Iyanku leaves, botanically identified as Clerodendrum inerme and Azima tetracantha in the Sampasivampillai Dictionary. This study aimed to assess scientifically the four types of salt forms (S 1- S4) utilized in Siddha diets, crude salt, thermally processed salt, and salt processed with Clerodendrum inerme, and Azima tetracantha. All four preparations were evaluated by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and high-performance thin-layer chromatography (HPTLC). Aqueous solubility was observed across all samples. Evaluation of the organoleptic properties revealed that S1 and S2 were white crystalline structures, while S3 was a pale white crystalline structure and S4 was a pale whitish-grey crystalline structure. SEM analysis demonstrated a progressive reduction in particle dimensions: S1 (64.60 -140.1 μm) S2 (33.37- 53.01 μm), S3 (43.13 - 68.76 nm), and S4 (130.6 - 419.1 nm), which may enhance bioavailability. FTIR spectra confirmed O–H stretching bands in S1, S3, and S4, whereas S2 displayed an aromatic NH2 vibration indicative of primary amines. The HPTLC six distinct peaks for S3 and eight for S4, confirming the integration of diverse plant-derived secondary metabolites during herbal processing. Complementary spectroscopic and chromatographic analyses successfully validated the structural and chemical modifications driven by traditional processing techniques. Further analyses can offer valuable insights into the specific pharmacological actions of these compounds.
Keywords: Azima tetracantha; Clerodendrum inerme; Salt; Siddha medicine; Siddha medicine; Phytochemical